Tract(atus) 23: Theorie is wachten - Grelet, Gilles; MuKHA, MuKHA (Identities: Journal for Politics, Gender and Culture, 2018)
Author(s): Gilles Grelet Title (Dutch): Tract(atus) 23: Theorie is wachten Translated by (French to Dutch): MuKHA Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 111 Page Count: 1 Citation (Dutch): Gilles Grelet, “Tract(atus) 23: Theorie is wachten,” vertaald uit het Frans door MuKHA, Identities: Journal for Politics, Gender and Culture, Vol. 15, No. 1-2 (Summer 2018): 111.